Analisis Adopsi Teknologi Tanpa Uang Tunai Di Unit X PT Y - Anindhita Satria Mahendra; Arief Rahman (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
This research delves into the adoption of non-cash payment technology at X Unit of PT Y. Its benefits encompass streamlined income reporting, transaction security, and efficiency. However, challenges include additional infrastructure costs, robust internet connectivity requirements, occurrences of double payments, and reconciliation issues in financial reports. Proposed solutions include installing additional ATMs, collaborating with banks, and hiring Information and Technology (IT) personnel. Applying the Technology, Organization, and Environment (TOE) theory, the research analyzes factors influencing technology adoption in the tourism industry. In conclusion, introducing non-cash payment systems to tourists is essential to enhance service effectiveness and financial management at Prambanan. This study significantly contributes to understanding obstacles and solutions in adopting non-cash payment technology in the tourism industry, offering a strategic framework for sustainable development in the future.